(3eWdY GdHOhQ heLeY GdHMhQs - (3CMeO Hf UGdM Hf CHj GdQLGd Gdjefj, Uaj GdOjf ,GHf nCHj GdpqQnLGd,J (B1092 (3g` s ((3YHO GdbGOQ Hf Ydi Hf GdMSjf Hf (B( (3CejQ GdeDefjf(B) (3GdegOi CMeO Hf GdMSf Hf GdbGSe Hf eMeO hhdOg GdMjSf Hf YHO GdbGOQ GdMSf Gdjefi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd YdeGA GdYJQI ddMb YdeG hdbO JLGSQJ Ydi gPG Gdfbd , deG QCjJ dHYV GdYdeGA ef GdMfajI eKdI , hGHJOCJ HEHQGgje Hf CHj GdaJhM s
(3BNQgG (B:s
(3Ke bGdJ (B: (3Ef CQOJ GdJeGdc gGfJ Ydjg gHI GdahWI hGdTedI hehdGfG jgJR ddfOi hGdSdGe ced GdLRA GdChd ef eWdY hGdMeO ddg s
(3GdUaMI GdChdi eRhbIs
(3HChdgG agQS ddeJQLejf ai SHY hQbGJs
(3ai GdeYgO fSNI CNQi HQbe (B1231 (3JGQjN LeY ajg JQGLe CYjGf habgGA GdRjOjI HGdjefs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdJGQjNs